The Tissue Selective Estrogen Complex: A Promising New Menopausal Therapy - Sebastian Mirkin; Barry S. Komm (MDPI AG, 2012)
Menopause is associated with health concerns including vasomotor symptoms, vulvar/vaginal atrophy (VVA), and osteoporosis. Estrogen therapy or combined estrogen-progestin therapy (EPT) are primary treatment options for menopausal symptom relief and osteoporosis prevention. Because EPT has been associated with some safety/tolerability concerns relating to undesirable effects of estrogen and progestin, alternative options are needed. The tissue selective estrogen complex (TSEC) is a novel class of agents pairing a selective estrogen receptor modulator (SERM) with 1 or more estrogens. The TSEC combines the established efficacy of estrogens on menopausal symptoms and bone with the protective effects of a SERM on the reproductive tract. The pairing of bazedoxifene (BZA) with conjugated estrogens (CE) has been evaluated in a series of phase 3 clinical trials. BZA 20 mg/CE 0.45 mg and BZA 20 mg/CE 0.625 mg have shown efficacy in reducing the frequency and severity of hot flushes, relieving VVA symptoms, and maintaining bone mass while protecting the endometrium and breast. These BZA/CE doses have been associated with a favorable safety/tolerability profile, with higher rates of cumulative amenorrhea and lower incidences of breast pain than those reported for EPT. Thus, BZA/CE may be a promising alternative to conventional EPT for treating non-hysterectomized, postmenopausal women.